Confirmatory Factorial validity of Neighborhood Features amongst South Africa low-income Housing Occupants’ - Aigbavboa, Aigbavboa (Journal of Economics and Behavioral Studies, 2013)
There is a fundamental link between theory and measurement advising that factorial confirmation of measures should be the first stage of theory testing. The aim of this paper was to confirm the factorial validity of the neighborhood features in a residential satisfaction study amongst South Africa low-income housing occupants’. The study was conducted amongst subsidized low-income housing occupants’ in South Africa. Data used in the study were obtained from a Delphi and field questionnaire study. Primary data was collected through the use of a structured questionnaire survey conducted among 751 low-income housing residents’ in three metropolitan and one district municipality in the Gauteng Province of South Africa. Data gathered via the questionnaire survey were analyzed using structural equation modeling (SEM) which was used to confirm the factorial structure of the constructs. SEM analysis revealed that the Rho coefficient and the Cronbach’s alpha coefficient of internal consistency were over 0.70 criterions for acceptability. Further finding was that neighborhood features influence on the residents’ satisfaction was not statistically significant and hence was weak in the prediction of the residents’ satisfaction with their houses. However, due to the idiosyncratic dataset used in the study, it remains to be seen if the evaluated indicator factors of neighborhood features can replicate to other cross-cultural datasets. If this is the case, the paper makes a significant contribution towards understanding neighborhood features on subsidized low-income housing projects. This study provided significant insight into how residents’ satisfaction with their houses could be improved.